Development of molecular platform for the detection of harmful algal bloom species, Alexandrium minutum / Winnie Lau Lik Sing - Winnie Lau, Lik Sing (2017)
Toxic marine dinoflagellate Alexandrium minutum is widely associated with paralytic shellfish poisoning (PSP) in the Asia Pacific region. This species have been reported for PSP cases at east coast of Peninsular Malaysia. In this study, a powerful and advanced method was demonstrated for the detection of A. minutum using SYBR Green I-based quantitative real-time PCR (qPCR) and investigates the life cycle of A. minutum in natural bloom using flow cytometry. For qPCR detection, species specific primers were designed from second internal transcribed spacer (ITS2) region of ribosomal RNA gene (rDNA) which had been showed to be the excellent molecular signature for species identification and discrimination. The qPCR assay showed high specificity and sensitivity in detecting A. minutum from the environmental samples. This assay allow quantification of target cells by convert total extractable gene copies into cell number based on the extractable gene copy number per cell estimated in the studies. Gene-based calibration curve with AE 97.6% was served as an alternative calibrator in A. minutum qPCR quantification. Based on the calibration curve, the assay estimated 7,584 ± 1,139 extractable gene copies per cell of A. minutum. However, the gene copy number per cell determined is only an estimate to convert the total extractable gene copies in a sample to cell estimates. In addition, SYBR Green I-based qPCR assay was applied to the A. minutum bloom samples. However, overestimation and underestimation in some samples were observed due to different DNA content at different stage of life cycle. Specificity and sensitivity of the assay provide an effective method for A. minutum monitoring especially in the site with different Alexanderium spp. coexist. In early September 2015, a remarkably high density of A. minutum occurred in Sungai Geting, Tumpat, a semi-enclosed lagoon at north-eastern Peninsular Malaysia, causing severe discoloration and contaminated the benthic clam, Polymesoda similis. Samplings were undertaken over the duration of four months between the bloom periods from September to December 2015. Plankton samples were collected and used to investigate the mechanisms of blooms initiation, development and termination by flow cytometry based detection. A 48-h sampling was conducted in March 2016 when the bloom recurred to investigate the life cycle stage. Results from flow cytometric analysis showed that planomyocetes (4C) were observed (88%) in the early bloom, suggesting that the bloom was initiated by cyst excystment. Increase in planozygotes (2C) was signified in the middle of the bloom, coincided with an abrupt decrease in salinity and elevated N:P ratio. Gamate expression and mating process were induced among the population under phosphorous limitation. The results also confirmed that the bloom was initiated at the inner part of the lagoon and slowly dispersed to the river mouth. The blooms were sustained for four months by 72 92% of vegetative cells (1C) although 36% of planozygotes (2C) were observed in the early of the bloom. Results from the 48-h diurnal sampling confirmed that cells undergo consistent cell cycle in natural environment. Increase of precipitation and freshwater intrusion from the Golok River might cause the bloom to terminate. This event provides a fundamental understanding of the life cycle of this tropical toxic dinoflagellate.